The Bacterial Microflora of Fish, Revised. (2006) - Austin, B.
Abstract : The results of numerous studies indicate that fish possess bacterial populations on or in their skin, gills, digestive tract, and light-emitting organs. In addition, the internal organs (kidney, liver, and spleen) of healthy fish may contain bacteria, but there is debate about whether or not muscle is actually sterile. Using traditional culture-dependent techniques, the numbers and taxonomic composition of the bacterial populations generally reflect those of the surrounding water. More modern culture-independent approaches have permitted the recognition of previously uncultured bacteria. The role of the organisms includes the ability to degrade complex molecules (therefore exercising a potential benefit in nutrition), to produce vitamins and polymers, and to be responsible for the emission of light by the light-emitting organs of deep-sea fish. Taxa, including Pseudomonas, may contribute to spoilage by the production of histamines in fish tissue.